Determinants of ESG Disclosure: An Empirical Study of Companies in 2 Asean Countries - Mey Ayu Lestari; Agrianti Komalasari; Reni Oktavia (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze Gender diversity, Institutional Ownership, and Governance Committee on ESG Disclosure in the mining sector in Indonesia and Malaysia in the 2019-2023 period. The type of the research is quantitative (desk research) based on secondary data The Data This study used mining sector companies in Indonesia and Malaysia from 2018 to 2023 with a total of 195 samples. The sample was derived using a purposive sampling technique. Panel data regression analysis is carried out using Eviews 13 in this study. This study finds that gender diversity and institutional ownership significantly negatively affect ESG disclosure, while the governance committee has a significant positive effect on ESG disclosure. Limitations in this study able to be provided by measuring ESG disclosure using the GRI standards. This research can be used as a literature reference for further research in studying ESG disclosure; besides, this research can be used as a consideration for stock investors in analyzing ESG disclosure.